1994
DOI: 10.1063/1.358381
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous interface magnetism in ultrathin Co films with in-plane anisotropy

Abstract: Articles you may be interested inStudy of in-plane magnetic anisotropy of ultrathin epitaxial Fe films grown on vicinal Mo(110) surface J. Appl. Phys. 95, 7312 (2004); 10.1063/1.1652411 Magnetic anisotropy engineering in in-plane magnetized ultrathin ferromagnetic films (invited) Influence of surface atomic steps on inplane magnetic anisotropy of ultrathin Fe films on W(001)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…Since that time, the impact of the reduced symmetry at surfaces [2 -4], interfaces [5], and thin films [6] on interfacial magnetic moments has been of major interest. For example, variation in the magnetic anisotropy or exchange coupling is observed as foreign atoms are adsorbed onto clean 3d magnetic surfaces [7][8][9], thereby allowing surface and thin film magnetic properties to be tailored. It is known that such phenomena result from the spin-orbit coupling between orbital and spin moments near the surface [6,10].…”
mentioning
confidence: 99%
“…Since that time, the impact of the reduced symmetry at surfaces [2 -4], interfaces [5], and thin films [6] on interfacial magnetic moments has been of major interest. For example, variation in the magnetic anisotropy or exchange coupling is observed as foreign atoms are adsorbed onto clean 3d magnetic surfaces [7][8][9], thereby allowing surface and thin film magnetic properties to be tailored. It is known that such phenomena result from the spin-orbit coupling between orbital and spin moments near the surface [6,10].…”
mentioning
confidence: 99%
“…We first observe that M(H) loops in the ͓110͔ direction are not fully square, in contrast to the usual easy magnetization behavior for the Co/ Cu͑001͒ system, where fcc Co has a large in-plane fourfold anisotropy and its easy axes lie along the ͕110͖ crystallographic directions. 4 This indicates that the magnetic easy axis of the fcc Co͑001͒ departs from the fourfold ͓110͔ easy axis. M(H) loops in the ͓100͔ direction for the uncovered Co are also nearly square and fully saturated at 250 Oe.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] Much attention has been recently given to studies of the structure and magnetism of two-dimensionally ͑2D͒ ordered surface alloys based on transition metals, since they provide important insights into the effects of the adsorbed nonmagnetic atoms on the magnetic ordering in ultrathin magnetic films. 5,6 A wide range of Mn surface alloys, based on Mn/Cu͑001͒, Mn/Ni͑001͒, and Mn/Fe͑001͒, [6][7][8][9] have been studied theoretically and experimentally, both because of a rich variety of possible structural and magnetic phases occurring in epitaxially grown Mn films and because a large magnetic moment can form due to the half-filled 3d shell of Mn.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, careful structural studies by Kief and Egelhoff 22 showed that surface segregation of Cu occurs at elevated temperatures. Schumann et al later demonstrated that the deposition of submonolayer coverages of nonmagnetic Cu on fcc Co͑001͒ ultrathin films with in-plane anisotropy can cause a reduction in the Co layer coercivity by ϳ300% for appropriate Co layer thicknesses, 23 illustrating how dramatic overlayer induced effects can be. This result can be used to explain the temperature dependence of the coercivity and is believed to arise from the preferential nucleation of Cu at edge sites provided by atomic steps in the Co film.…”
Section: Interface Induced Magnetic Anisotropiesmentioning
confidence: 99%